Pengaruh Profitabilitas, Ukuran Perusahaan dan Likuiditas terhadap Harga Saham - Fadhila Annisa Pranandyasari; Munari Munari (Universitas Batanghari Jambi, 2023)
The purpose of this study is to investigate how profitability, firm size, and liquidity affect stock prices. This study uses infrastructure companies that will be listed on the Indonesia Stock Exchange in 2021 as the population. Purposive sampling is the method of sampling that is used. A method of sampling called